2015
DOI: 10.1002/jor.23079
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage degeneration and excessive subchondral bone formation in spontaneous osteoarthritis involves altered TGF-β signaling

Abstract: Transforming growth factor-b (TGF-b) has been demonstrated as a potential therapeutic target in osteoarthritis. However, beneficial effects of TGF-b supplement and inhibition have both been reported, suggesting characterization of the spatiotemporal distribution of TGF-b during the whole time course of osteoarthritis is important. To investigate the activity of TGF-b in osteoarthritis progression, we collected knee joints from Dunkin-Hartley (DH) guinea pigs at 3, 6, 9, and 12-month old (n ¼ 8), which develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 36 publications
(35 reference statements)
3
62
0
Order By: Relevance
“…In contrast, the chemical inducers may show inhibitory effects instead of stimulation. For example, synovial fibrosis, osteophyte formation, cartilage degeneration or bone remodeling has been previously reported for altered signaling in TGF-β concentration 36 . Furthermore, it has been reported that degeneration of cartilage in osteoarthritis cases can be reduced by inhibition of TGF-β signaling in subchondral bone 37 .…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the chemical inducers may show inhibitory effects instead of stimulation. For example, synovial fibrosis, osteophyte formation, cartilage degeneration or bone remodeling has been previously reported for altered signaling in TGF-β concentration 36 . Furthermore, it has been reported that degeneration of cartilage in osteoarthritis cases can be reduced by inhibition of TGF-β signaling in subchondral bone 37 .…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, TGFβ signaling through the smad2/3 pathway is its canonical pathway. Therefore, in present study, the expression of TGFβ1 and pSmad2/3 was detected by immunohistochemistry with reference to previous research findings (8,9,12). Although statistical correlation and in vitro analysis were performed to determine the effect of activating osteocyte TGFβ signaling pathway on osteogenesis and osteoclast differentiation, a direct relationship between osteocyte TGFβ signal and the development of OA remains to be elucidated.…”
Section: Ratio Of P-smad2/3-positive Osteocytes Bone Turnover -------mentioning
confidence: 91%
“…Transforming growth factor β (TGFβ), canonically binds to its cell surface receptor and then directly phosphorylates Smad2/3 to translocate the signaling molecule into the nucleus and interact with other transcriptional factors, playing an important role in the development of OA (8)(9)(10)(11)(12)(13). However, the effect of TGFβ on OA varies depending on the sites it acts on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While required for early chondrogenesis, signaling through ALK 1, and subsequent phosphorylation of SMAD 1/5/8 has been implicated in the terminal differentiation of MSCs . Furthermore, the impact of TGF‐β on chondrocyte differentiation may be altered in response to aging and increasing evidence implicates altered TGF‐β signaling in the progression of OA . Dynamic mechanical compression at 1 Hz with 3 MPa stress has been previously reported to activate the ALK 5/SMAD 2/3 signaling pathway in bovine articular cartilage explants, highlighting a protective effect of mechanical stimulation on articular cartilage .…”
Section: Role Of Mechanical Stimulation and Cartilage Developmentmentioning
confidence: 99%